Mechanisms or ways of developing and improving the security culture - Stanarevic, Svetlana S (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
In this text we will try to explain and recommend the ways in which security culture can be developed or promoted. Namely, within security studies this concept is most commonly represented as a means or analytical framework of understanding changes occurring in the security sphere over time. However, we would like to underscore the importance of viewing and applying security culture as an instrument of bringing about change, which could prove significant at a time (such as the present) when turbulent events are happening all over the world, carrying serious security implications. As well as analytical potential, the concept of security culture offers normative potential and in that regard it is important to determine all the mechanisms and factors that can contribute to its development and promotion. In this paper, we have chosen to present the role and significance of the national educational system, the establishment and development of standards, the introduction of a control mechanism and commitment. The elected mechanisms and/or factors are relevant as they satisfy he need for certain kinds of knowledge and skills, ensure that security measures, rules, procedures and expectations are followed and met, encourage behavior by which set values are up held ,and show long-term commitment to creating an open and trusting environment that is proactive and focused on reducing risks and threats to the well-being of all.